Determination of chemical composition and potential anticancer activities of Allium atroviolaceum extract on selected cancer cell lines - Khazaei, Somayeh (2016)
The present study was carried out to determine the phytochemicals and the chemotherapeutic potentials of Allium atroviolaceum flower (FA) and bulb (BA) cruden extracts in selected reproductive cancer cell lines, human hormone dependent breast cancer (MCF7), human hormone independent breast cancer (MDA-MB-2341), human cervical cancer (HeLa), and human liver cancer (HepG2) and non-malignant murine fibroblast (3T3) cell lines. The extracts were found to induce anti-proliferative effect on all the studied cells. 70% methanol extracted after 9 hours gave the most promising IC50 values. Exposure of breast, cervical, and liver cancer cell lines to FA and BA extracts demonstrated growth inhibition of cells in both dose- and time-dependent manners. The IC50 value for each cell line at 24, 48, and 72 hours respectively, is given as follows: MCF7 (65, 41, and 24 μg/ml for FA, while 91, 88, and 75 μg/ml for BA), MDA-MB-231 (77, 67, and 51 μg/ml for FA, while 150, 114, and 101 μg/ml for BA), HeLa (68, 51, and 37 μg/ml for FA , while 100, 98, and 74 μg/ml for BA), and HepG2 (57, 44, and 26 μg/ml for FA, while 97, 70, and 58 μg/ml for BA). On the other hand, the IC50 value of normal 3T3 cell line was found to be > 100, indicating that FA and BA extracts were not cytotoxic to normal cells. In addition, the interaction of FA and BA extracts with tamoxifen (against MCF7 and MDA-MB-231) and doxorubicin (against HeLa and HepG2) revealed a significant dose-reduction in IC50 value. Phase contrast and fluorescent microscopy (AO/PI) analyses demonstrated apoptotic features after treatment with FA and BA for 24, 48, and 72 hours. Analyses of DNA content and cell cycle with PI staining confirmed that the time and dose course treatments of FA and BA crude extracts displayed the ability in promoting S phase arrest, G2/M phase arrest, as well as apoptosis in MCF7, MDA-MB-231, and HepG2. However, the event was both time- and dose-dependent, although G0/G1 phase arrest was observed in HepG2 treated with BA in low concentration. Meanwhile, in HeLa cells, the extract enhanced only the percentage of cells present in sub-G0 in both time- and dose-dependent manners. The Annexin V assay revealed that FA and BA extracts induced cell death by stimulating early apoptosis in low and middle concentrations (IC25 and IC50), as well as shorter incubation time (24 and 48 hours), while inducing late apoptosis/necrosis in high concentration (IC75) and longer time course (72 hours) in all the cell lines. The effect of FA and BA extracts at 24 hours on activity caspases illustrated that the apoptotic effects of FA and BA were via activation of specific inflammatory and initiator caspase, which led to the activation of final effector, caspase-3 or 6. In some cases, increment of caspase-8 and -9 activities indicated that both extrinsic and intrinsic pathways were activated by those extracts that were depended on the type of cell lines. Moreover, the activity of caspase-3 as the main executioner caspase was evaluated with more time course, 48 and 72 hours. As a result, more time of exposure to both FA and BA led to less caspase-3 activity in MCF7 and HeLa, while in MDA-MB-231 and HepG2, longer time incubation resulted in more activities of caspase-3 executioner caspase. In addition, gene expression analysis using the qPCR conducted on three target genes (BCL2, CDK1, and p53) showed downregulation of anti-apoptotic BCL2 in MCF7, MDA-MB-231, and HeLa, while only FA-treated HepG2 exhibited enhanced apoptosis. Additionally, upregulation of p53 only after treatment with BA in MDAMB- 231 and HepG2 illustrated induced apoptosis through a p53-dependent mitochondrial pathway, while p53-independent mitochondrial pathway in other treated cells. More to the point, CDK1 was downregulated in MCF7, MDA-MB-231, HeLa, and slightly in HepG2 after exposure to both extracts that might be the main mechanism used by both extracts to exert G2/M cell cycle arrest and ultimately, the final fate of cells, apoptosis.